Using n-alkanes as a proxy to reconstruct sea-level changes in Thale Noi, the west coast of the Gulf of Thailand. (15th June 2021) - Sainakum, Assuma; Jittangprasert, Piyada; Sompongchaiyakul, Penjai; Jirapinyakul, Akkaneewut
Highlights: n-Alkanes were analyzed and used to reconstruct the sea-level changes on the Gulf of Thailand c. 8300-6870 cal. a BP. The n-alkanes analysis agreed well in time with other records and pointed to regression c. 8300–7950 cal. a BP and transgression c. 7920–7665 cal. a BP. Pollen records indicated a standstill of sea-level c. 7650-6870 cal. a BP, while the sea-level fluctuations during this interval can be reconstructed by nalkanes analysis. The various ranges of environmental responses of paleoproxies are a possible explanation of these discrepancies. Abstract: The n-alkanes content in the sedimentary sequence from Thale Noi, on the west coast of the Gulf of Thailand, was analyzed and used to reconstruct the past sea-level fluctuations. The results were further compared with those based on sediment characteristics, loss on ignition, grain size distribution, and pollen analysis from the same core to investigate the efficiency of n-alkanes as a paleoenvironmental proxy. The analysis of n-alkanes indicated the likely periods of regression and transgression from c. 8300–7950 cal. a BP and from c 7950–7665 cal. a BP that agrees well with the reconstructed sea-level changes from the sediment characteristics and pollen records. The steady abundance of mangrove pollen taxa in the sediment core points to a standstill in the sea-level from 7650–6870 cal. a BP. However, the results from the n-alkanes analysis further suggested a sea-level fall at c. 7650–7610 cal. a BP and at c. 7400–6870 cal. a BP, and a sea-level rise at c. 7610–7400 cal. a BP. Furthermore, these sea-level changes were intervened by short intervals of regression centered at c.7590 and 7470 cal. a BP.